غلام محمد قاصر کے کلام میں عصری معنویت: Contemporary Relevance in the Poetry of Ghulam Muhammad Qasir (Al-Aasar, 2025)
This article explores the poetic vision of Ghulam Muhammad Qasir, who is considered one of the most prominent voices of modern Urdu ghazal. Qasir’s poetry strikes a balance between tradition and modernity, preserving the classical form of the ghazal while infusing it with fresh sensibilities, modern diction, and contemporary socio-political consciousness. His ghazals reflect love, loneliness, exile, existential angst, and socio-political critique. By using simple yet powerful imagery, Qasir transforms individual pain into a collective narrative. The study    argues   that Qasir not only represents the transition of Urdu ghazal from classical to modern aesthetics but also establishes a distinctive voice that resonates with the struggles and aspirations of his era.